A Numerical Method for Coupled Cardiac Electro-Mechanical Simulations - Whiteley, J; Pathmanathan, P; Simos, T (2010)
A heartbeat is the consequence of cardiac tissue deforming in response to tension generated in cardiac fibres. This tension is a result of biochemical reactions that occur as part of cardiac electrophysiology. This coupled electro-mechanical system is usually modelled by coupling a model of tissue deformation with a tissue level model of cardiac electrophysiology such as the bidomain equations [1]. One difficulty with computing a numerical solution of this coupled system is numerical stability [3, 7]. In this paper we describe how numerical stability may be attained by embedding the model of generation of active tension within the tissue deformation model. © 2010 American Institute of Physics.